Structural Change in the Import Demand Function for Pakistan (The Pakistan Development Review, 1991)
The question of structural stability of the Aggregate Import Demand Function (IOF) has important implications for modelling, forecasting as well as policy- making related to the trade sector, in general and imports in particular. A structural change, in quantitative terms, may be reflected as a change in one or more parameters of the import demand function. Analysing the possibilities, timing and the nature of such a change is important since it affects the estimates of the relevant elasticities. In the case of Pakistan, the issue of the possible structural change in the IOF has not been studied much in spite of its importance. The two notable exceptions are Sarmad (1989) and Naqvi and Khan (1989). In Sarmad (1989) while the main purpose was to choose between the linear and log-linear functional forms for the IOF there is incidental treatment of structural change when he specifies a dummy to account for the dislocation of economic activity caused by the separation of East Pakistan in 1971. Thus he implicitly hypothesizes that structural change occurred only in term of the intercept.1 However, he also reports that there may have been a structural shift in 1982-83 in the import demand for manufacturing. Again, Naqvi and Khan (1989) report a significant 1971-72 dummy coefficient in case of imports of manufactured goods and significant 1972-73 dummy Jor imports of services adjusted for interest payment on foreign debt.